Dampak Leverage, Profitabilitas, Likuiditas dan Ukuran Perusahaan Terhadap Kualitas Laba - Sejati, Fajar Rina; Sutisman, Entar; Pertiwi, Dian; Ponto, Sahrul; Syamsuddin, Nurul Hidayah (Public Policy, 2021)
The purpose of this study was to examine the effect of leverage, profitability, liquidity, and company size on earnings quality. The sample of this study was using 11 companies in the property, real estate & building construction sub sector service companies listed on the Indonesian Stock Exchange (IDX) during 2014-2019 period met all the criteria. Empirical evidence suggest that leverage and profitability has no effect on earnings quality. Then, liquidity has negative effect on earnings quality and company size has positive effect on earnings quality.